The Impact of Lean Practices on Quality and Business Performance in Malaysian Manufacturing Industry - Iteng, Rosman; Ariffin, Ahmad Shabudin; Mohd Asaad, Mohd Norhasni; Ahmad, Mohd Akhir; Abdul Rahim, Mohd Kamarul Irwan (UUM, 2021)
The primary purpose of this research is to examine the relationships between lean practices, quality and business performance in Malaysian manufacturing companies. This study applies the Sociotechnical System Theory and the Program Theory to formulate and examines a conceptual model that links lean practices, quality performance and business performance. Although the theories imply that there is a positive relationship between lean practices with organizational performance, some results from recent studies suggest that the relationship is not conclusive. This study utilizes two hundred and five sample data which are randomly selected from companies listed in the directory of Federation of Malaysian Manufacturers. This study applies SPSS package for data analysis. The result indicates that lean practices significantly relate to quality and business performance of the manufacturing companies in Malaysia. The finding also suggests that quality performance mediates the relationship between lean practices and business performance. The result also demonstrates a significant relationship between quality performance and business performance. This study presents empirical evidence in the field of management, particularly in the context of operations management. The findings would further enrich the existing knowledge in this field. Finally, this study would provide useful guidance for the managers to plan and maintain lean production in the organization as well as to generate new measures of lean practices in order to enhance business performance at the company level.